Trichoderma: A biocontrol for Preventing Plant Diseases and Advancing Sustainability (Review article) - Jassim, Naji S.; Jaafer, Mahmood Oda (Basrah Journal Of Date Palm Research, 2023)
Trichoderma species serve as effective biocontrol agents and successful symbiotic organisms with host plants that are also cost-effective, and helpful to the environment and they did not harm the beneficial species. In addition to boosting growth and yields, this symbiotic interaction between plants and Trichoderma also promotes nutrient uptake and efficient fertilizer use. Additionally, it causes plants to become more resistant to disease. Antibiosis, competition for nutrients and space, and mycoparasitism are a few of the primary ways that Trichoderma with other competing plants pathogens by inhibiting or blocking their growth. The production of specific metabolites, such as plant growth regulators, enzymes, siderophores, antibiotics, etc., is required for the stimulation of every process against phytopathogens. The review emphasizes the relevance of employing Trichoderma fungus for environmental purposes at the biochemical and molecular levels in the impacted root zone. It also offers a general summary of Trichoderma's utility as a biological control agent. The information presented here strongly suggests that Trichoderma could be used as a secure, environmentally acceptable, and influential biocontrol agent for many crops various.